Enantioselective Cobalt‐Catalyzed Intermolecular Hydroacylation of 1, 6‐Enynes. Issue 38 (20th July 2020) - Whyte, Andrew; Bajohr, Jonathan; Torelli, Alexa; Lautens, Mark
Abstract: We report a cobalt‐catalyzed hydroacylation of 1, 6‐enynes with exogenous aldehydes in a domino sequence to construct enantioenriched ketones. The products were obtained in good yields with excellent regio‐, diastereo‐, and enantioselectivity. Furthermore, the chiral products served as valuable precursors to access complex spirocyclic scaffolds with three contiguous stereocenters. The asymmetric hydroacylation process exhibited no C−H crossover and no KIE, thus indicating that the C−H bond cleavage was not involved in the turnover‐limiting step. Abstract : A cobalt‐catalyzed domino cyclization/ C−H functionalization of aldehydes is reported. The cascade reaction shows high regio‐, diastereo‐, and enantiocontrol towards enantioenriched heterocycles. The enones are readily diversified to furnish complex spirocycles. Preliminary mechanistic studies are also reported.